PEMBERDAYAAN KADER DALAM PENINGKATAN PENGETAHUAN, SIKAP, PRAKTIK IBU TENTANG PENCEGAHAN KANKER PAYUDARA - Mahmudah, Mahmudah; Fibriana, Arulita Ika (Journal of Health Education, 2018)
Breast cancer now still as a big problem in world or Indonesia. Morbidity rate and mortality rate are increase. Breast cancer incidence in Pemalang city in 2014 was 247 cases increased  273 in 2015, in Mulyoharjo health center own well acquired cases of cancer by as much as 61 cases.  The purpose of this study was to determinane differences in knowledge, attitudes and practice among mother about breast cancer prevention before and after health volunteers empowerment.  This research is quasy eksperiment. With delightful pretest-posttest control group design. The technique of using purposive sampling. Samples consisting 0f 30 people group of 30 people group of experimentation and 30 people the control group. Instrument research using a questionnaire knowledge, attitude and practice about breast cancer prevention. The independent variable was health volunteers empowerment, the dependent variable was knowledge, attitude and practice about breast cancer prevention. The analysis used in this research were Mc Nemar and chi square. The result showed knowledge about breast cancer prevention of each group was different significantly (p=0,024), attitude about breast cancer prevention of each group was no difference (p=1,000), and practice about breast cancer prevention of each group was different significantly (p=0,041).  The conclusion of this research is health volunteers empowerment influential in increasing the konowledge and practice in the prevention of breast cancercompared with those who do not health volunteers empowerment.   Keywords : Breast Cancer, Knowledge, Attitude, Practice, Health volunteers empowerment. Literature : 41 (2001-2015).